Juridical Analysis of Efforts of Increasing Regional Genuine Income Through Revenue of Tax Taxes For Land and Building Rights Acquisition (BPHTB) in Regional Revenue, Financial and Asset Management Agency (BPPKAD) - Haryanto, Dyan Dwi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
BPHTB is categorized as Regional Tax revenue, which in its entirety is included in the PAD component. After the enactment of Act No. 1 of 2022, In this case, it is hoped that the transfer of BPHTB taxes from central taxes to local taxes can make a major contribution in increasing regional original income and aims to increase the local taxing power of districts/cities. This makes the regional government more autonomous, not only on the expenditure side, but also on the revenue management side. The changes in various national policies as referred to have brought great hope for the regions to develop their regions by exploring the potential of their respective regions as sources of regional income, especially regional original income through the tax collection policy of Land and Building Rights Acquisition Tax (BPHTB). The approach method used in this research is a sociological juridical approach. The sociological juridical approach is a research that identifies and conceptualizes law as a real and functional social institution in a real-life system. This study identified the main meanings in law such as legal subjects, rights and obligations, legal events in laws and regulations. This research is based on the science of normative law (laws and regulations), especially examining the reactions and interactions that occur when the norm system works in society. From the definition of self-assessment, it can be concluded that in the implementation of tax collection BPHTB requires taxpayers to understand and master the tax provisions as stipulated in the applicable tax laws and regulations, so that with the existence of this self-assessment system, it is possible that taxpayers will experience difficulty in paying the tax.Keyword: Effectiveness; Revenue; Tax.